Negative language use of the physiotherapist in low back pain education impacts anxiety and illness beliefs: A randomised controlled trial in healthy respondents. (May 2023) - (Fieke) Linskens, F.G.; van der Scheer, E.S.; Stortenbeker, I.; Das, E.; Staal, J.B.; van Lankveld, W.
Abstract: Objective: This study aimed to determine the effect of physiotherapists' negative language use on nocebo effects of state anxiety and illness beliefs. Methods: A web-based randomised controlled trial included adults without recent musculoskeletal pain. The intervention was a short educational video about low back pain using negative language (nocebo condition: n  = 87) versus a video using neutral or positive language (control condition: n  = 82). State anxiety was assessed using the State-Trait Anxiety Inventory. Illness beliefs were assessed using the Illness Perception Questionnaire. Results: Nocebo and control groups differed in outcome measures (MANOVA Pillai's trace = 0.22, F = 4.98; df = (9, 159), p < 0.001). Post-hoc analyses showed a medium to large effect for the nocebo condition on anxiety (d = 0.71, 95% CI 0.4 –1.0). The nocebo group also had higher scores in three illness beliefs: beliefs on timeline (d = 0.45, 95% CI 0.14 – 0.75), treatment control (d = 0.43, 95% CI 0.12 – 0.74) and concern (d = 0.47, 95% CI 0.16 – 0.78). Conclusion: Physiotherapists' use of negative language contributes directly to a higher state anxiety and illness beliefs that can trigger the nocebo effects in the recipient Practice implications: Negative language use should be avoided. Highlights: Negative communication has an effect on state anxiety and illness beliefs in the recipient of the message. Nocebo communication (e.g., vague descriptions, negative language) resulted in higher state anxiety. Nocebo communication led to higher rates of concerns, and the belief that complaints would last longer. Nocebo communications led participants to believe that the treatment would be more successful.